Dual phylogenetic staining protocol for simultaneous analysis of yeast and bacteria in artworks - González Pérez, Marina (2018)
The detection and analysis of metabolically active microorganisms are useful to determine those directly involved in the biodeterioration of cultural heritage (CH). Fluorescence in situ hybridization with oligonucleotide probes targeted at rRNA (RNA-FISH) has demonstrated to be a powerful tool for signaling them. However, more efforts are required for the technique to become a vital tool for the analysis of CH’s microbiological communities. Simultaneous analysis of microorganisms belonging to different kingdoms, by RNA-FISH in-suspension approach, could represent an important progress: it could open the door for the future use of the technique to analyze the microbial communities by flow cytometry, which has shown to be a potent tool in environmental microbiology. Thus, in this work, various already implemented in-suspension RNA-FISH protocols for ex situ analysis of yeast and bacteria were investigated and adapted for allowing the simultaneous detection of these types of microorganisms. A deep investigation of the factors that can affect the results was carried out, focusing particular attention on the selection of the fluorochromes used for labelling the probe set. The resultant protocol, involving the use of EUK516–6-FAM/EUB338–Cy3 probes combination, was validated using artificial consortia and gave positive preliminary results when applied in samples from a real case study: the Paleolithic archaeological site of Escoural Cave (Alentejo, Portugal). This approach represents the first dual-staining RNA-FISH in-suspension protocol developed and applied for the simultaneous investigation of CH biodeteriogenic agents belonging to different kingdoms.